Neonatal sepsis and its associated factors among neonates admitted to the neonatal intensive care unit in Wachemo University Comprehensive Specialized Hospital, Southern Ethiopia, 2022 - Mezgebu, Taye; Ossabo, Getachew; Zekiwos, Asnakech; Mohammed, Hamdino; Demisse, Zerihun (Frontiers in Pediatrics, 2023)
Background Neonatal sepsis is a major public health problem worldwide. It is one of the leading causes of neonatal mortality and morbidity worldwide. The neonatal mortality rate is higher in developing countries, where the extent and causes of neonatal sepsis are not yet known. Neonatal sepsis is a leading cause of neonatal mortality in Ethiopia. As a result, this study aimed to assess the proportion and identify maternal and neonatal risk factors for neonatal sepsis among neonates admitted to the neonatal intensive care unit. Methods An institutional-based cross-sectional study was conducted from May 2022 to July 2022 at the Wachemo University Comprehensive Specialized Teaching Hospital, Neonatal Intensive Care Unit, southern Ethiopia. A total of 205 neonates with indexed mothers participated in the study. Using a consecutive sampling technique, a structured, pretested questionnaire was used to collect data from the study subjects. Data were entered into EpiData Manager version 3.1 for Windows and then exported to SPSS version 22 for further data cleaning and analysis. Descriptive analyses were performed by using frequency, percentage, and summary statistics to describe the key variables. A multivariate regression model was used to identify factors associated with neonatal sepsis. Finally, statistical significance was declared at a p-value of less than 0.05, and an adjusted odds ratio (AOR) with a 95% confidence level was used to declare the variable’s association with the outcome variable. Result The overall prevalence rate of neonatal sepsis was 39.5% (95% CI: 33.7–45.9). Multivariable analysis was performed by taking a variable that is statistically significant in bivariate logistic regression as a candidate variable. Multivariable model analysis showed that unmarried status AOR = 18.37 (95% CI: 1.56–216.14), maternal fever during delivery AOR = 4.74 (95% CI: 1.63–13.8), and premature rupture of membrane AOR = 7.53 (95% CI: 2.19–25.6) were variables that increased the odds of developing neonatal sepsis. Conclusion The study’s findings indicate that neonatal sepsis is highly prevalent. Unmarried maternal status, maternal fever during delivery, and premature rupture of the membrane were predictors of neonatal sepsis. Therefore, providing training for health workers and close monitoring and evaluation during obstetric and neonatal care are crucial to halt the occurrence of neonatal sepsis.